Pan-NLRome of Spinacia facilitates the rapid discovery of downy mildew resistance genes - She, Hongbing; Wang, Huiyu; Xu, Zhaosheng; Zhang, Helong; Liu, Zhiyuan (Frontiers in Plant Science, 2026)
Plant disease resistance is typically conferred by nucleotide-binding site leucine-rich repeats (NLR) proteins; however, the diversity of NLR genes in spinach has remained largely unexplored. We identified 2,549 NLR genes across 19 Spinacia assemblies of cultivated spinach and its two wild species, and constructed a comprehensive pan-NLRome, which was categorized into six subfamilies, and the most frequent NLR class was CC-NBARC-LRR. The pan-NLRome consists of 186 NLR families, comprising 38.7% core, 51.1% dispensable and 10.2% private families. By integrating pan-NLRome with k-mer-based genome-wide association studies (GWAS), we developed a novel pipeline for rapid identification of disease resistance genes. Using this approach, we directly pinpointed a candidate gene, Te17S24XX_Chr1_nlr42, for the RPF1 locus, which confers resistance to spinach downy mildew pathogen races 1–7, 9, 11, 13, 15, 16, 18, and 20. In contrast, a single-genome-based method identified four candidate genes, which required further analysis confirm the final gene. The Spinacia pan-NLRome serves as an invaluable resource for exploring NLR gene evolution and plant disease resistance mechanisms. Our developed pipeline offers a reliable and efficient strategy for cloning resistance genes across multiple crops.